Effect of Ability Grouping in Reciprocal Teaching Technique of Collaborative Learning on Individual Achievements and Social Skills - Sumadi Sumadi; I Nyoman S. Degeng; Sulthon Sulthon; Waras Waras (International Journal of Evaluation and Research in Education (IJERE), 2017)
This research focus on effects of ability grouping in reciprocal teaching technique of collaborative learning on individual achievements dan social skills. The results research showed that (1) there are differences in individual achievement significantly between high group of homogeneous, middle group of homogeneous, low group of homogeneous, and heterogeneous group in reciprocal teaching technique of collaborative learning, (2) there are differences in students social skills significantly between high group of homogeneous, middle group of homogeneous, low group of homogeneous, and heterogeneous group in reciprocal teaching technique of collaborative learning strategy. Based on the results of descriptive statistical analysis showed that individual achievements on high group of homogeneous turned out to mean the highest increase in the amount of 19.50, the second followed then a heterogeneous group with a mean increase of 15.00, the third then middle group of homogeneous with a mean increase of 13.50, and the lowest low group of  homogeneous with a mean increase of 11.75; the social skills on high group of homogeneous showed mean the highest increase in the amount of 10.92, the second a heterogeneous group with a mean increase of 8.75, followed middle group of homogeneous with a mean increase of 8.55, and the lowest of the low group of homogeneous with a mean increase of 6.71.